DETEKSI KEBERADAAN TELUR Soil Transmitted Helminth (STH) PADA KUKU PETANI - DITA PRATIWI KUSUMA WARDANI (Meditory : The Journal of Medical Laboratory, 2021)
Soil-Transmitted Helminth (STH) is an intestinal nematode that requires soil for the process of reproduction and maturation from non-infective to infective. The nematodes included in this species include Ascaris lumbricoides, Trichuris trichiura, and two species of hookworm, Necator americanus, and Ancylostoma duodenale. Personal hygiene can affect the incidence of helminth infections in humans. The purpose of this study was to determine the relationship between personal hygiene and the presence of Soil-Transmitted Helminth (STH) eggs on farmers' nails. This research was conducted by analytical observation with a cross-sectional design in April-May 2021. The research method was filling out questionnaires and identifying eggs using the 10% KOH sedimentation method. Data were analyzed by univariate and Pearson Chi-Square tests. The results of this study showed that 4 fingernail samples (47.05%) were positive for Ascaris lumbricoides eggs and 2 fingernail samples (11.76%) were positive for Minute Intestinal Fluke, as many as 8 toenail samples (82.35%) were positive for Ascaris lumbricoides eggs. and 1 sample of toenails (5.88%) positive for Minute Intestinal Fluke eggs. There was no relationship between personal hygiene and the presence of STH eggs on farmers' nails (p = 0.05). STH eggs were found in the fingernails and toenails of farmers in Kaligondang District, Purbalingga Regency. Farmers need to improve personal hygiene to avoid helminth infections.